Preobrazba podeželske kulturne pokrajine v Sloveniji - Kladnik, Drago (Georitem, 2009)
The book offers multi-layered responses to the scope and causes of spatial, as well as social, economic and physiognomic changes in the cultural landscape in Slovenian countryside. It presents the results of an interdisciplinary research approach to recognising spatial change and trends within a two-year research project entitled "The Transformation of the Landscape by Agricultural Modernisation and Changes in Settlement Patterns", which was financed by the Slovenian Research Agency and the Ministry of the Environment and Spatial Planning of the Republic of Slovenia within the target research programme Slovenian Competitiveness 2006-2013. Similar research was carried out in three pilot areas, selected because they captured a cross section of typical Slovenian landscape macro-units (Mediterranean, Dinaric, Alpine and Pannonian), while also covering the processes of intensification and marginalisation.